PENGARUH FRAKSI SERAT SABUT KELAPA DAN RESIN UNSURATED POLYESTER TERHADAP KEKUATAN TARIK KOMPOSIT - ., Sutrisno (JURNAL AGRI-TEK, 2015)
Coco fiber is a fiber that comes from nature at this time huge numbers and not dimanfatkan optimally. Fiber-style mini has a value ekonommis that tinngi when it can be processed into composite materials that can be utilized in automotive technology as well as for the other. To get a good composite material necessary technology is also good workmanship. Coco fiber is cleaned of flesh then made composites with polyester matrix BQTN. Methods of workmanship by means of hand lay up. Where the coconut coir fiber is set at a certain percentage of the variation of random fiber direction. Then they were then exposed to final touch according to standardized sizes for ASTM testing. Tensile testing according to ASTM D 638.The results showed that the volume fraction of 40% had the most excellent tensile strength that is equal to 14.8 MPA, the modulus of elasticity of 3.76 GPA. From these results can be concluded that the composite material can be used in the automotive industry as well as for domestic industry.Keywords: natural composites, coco fiber, polyester BQTN, tensile strength